Stress Concentration Factors at Two Radial Adjacent Nozzle-Header Connections of a Cylindrical Pressure Vessel. - Mohd Fadhlan bin Ismail, Mohd Fadhlan (Universiti Teknologi PETRONAS, 2008)
There are three major phases in completing project named, “Stress Concentration Factors at Two Radial Adjacent Nozzles Header Connections of a Cylindrical Pressure Vessel”. These three phases are; parameters specification, design and Finite Element Analysis (FEA). This report basically will summarize the activities that have been done to complete this project. In parameter specification phase, data acquired to design a two radial adjacent nozzles header connection of cylindrical pressure vessel was extracted from the standard nozzles and piping codes used in the industry. The required data and information for this project also been gathered by using all available resources. In design phase, the author will compiles all data and parameters gained and design a nozzles-pressured vessel configuration which will be the basis for the whole project. Finally, a FEA simulation will be done by using ANSYS to analyze the model and complete these project objectives. The design of nozzles in a pressure vessel is subjected to the internal pressure acting from all direction. But in this study, only the internal pressure effect will be considered. This project objectives are to analysis and investigate the stress concentration factors of two radial adjacent nozzles header connection of cylindrical pressure vessel result that come from internal pressure by using ANSYS and To study the result and effect of different nozzles inner diameter and size and displacement of these two nozzles so that, recommendation can be made to improve the design of two radial adjacent nozzle header connection of cylindrical pressure vessel. From this project, it is decided that stress concentration factor most occur at low value of L/d ratio which the distance between the two nozzle are closer.